2010
DOI: 10.1534/genetics.109.112029
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Candida albicans SNF7 Reveals Genetically Separable Rim101 and ESCRT Functions and Demonstrates Divergence in bro1-Domain Protein Interactions

Abstract: The opportunistic pathogen Candida albicans can grow over a wide pH range, which is associated with its ability to colonize and infect distinct host niches. C. albicans growth in neutral-alkaline environments requires proteolytic activation of the transcription factor Rim101. Rim101 activation requires Snf7, a member of the endosomal sorting complex required for transport (ESCRT) pathway. We hypothesized that Snf7 has distinct functions in the Rim101 and ESCRT pathways, which we tested by alanine-scanning muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 81 publications
(104 reference statements)
4
21
0
Order By: Relevance
“…4). This extends but is consistent with previously reported data from S. cerevi- (11,17,47,49). However, we noted that all of these mutants, excepting the mvb12⌬/⌬ strain, grew more poorly than did the rim101⌬/⌬ mutant on YPD pH 9, suggesting that these ESCRT pathway members have Rim101-dependent and -independent functions during alkaline growth.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4). This extends but is consistent with previously reported data from S. cerevi- (11,17,47,49). However, we noted that all of these mutants, excepting the mvb12⌬/⌬ strain, grew more poorly than did the rim101⌬/⌬ mutant on YPD pH 9, suggesting that these ESCRT pathway members have Rim101-dependent and -independent functions during alkaline growth.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies from our lab analyzed the effects of a variety of snf7 alleles on C. albicans-stimulated epithelial cell damage (47). These studies suggested that the only contribution of Snf7 to epithelial cell damage is Rim101 dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the snf7⌬/⌬ mutant failed to repress RIM8 (Fig. 7, lanes 15 and 16), as expected, since this mutant does not activate Rim101 (28,55). However, we found that the vps4⌬/⌬ mutant also failed to repress RIM8 (Fig.…”
Section: Fig 3 Genetic Requirements For Rim8 Modification Cells Exprsupporting
confidence: 84%
“…Rim101 activation requires the ESCRT-I, ESCRT-II, and ES-CRT-IIIa components of the ESCRT pathway (28,55,56,58). Thus, we asked if ESCRT components are required for Rim8 modification.…”
Section: Resultsmentioning
confidence: 99%